ANALISIS PENJADWALAN DENGAN METODE PRECEDENCE DIAGRAM METHOD (PDM) PADA PROYEK COMPACTOR ROLLER COMPACT MOULD - Rasyad Devala Jamaluddin; Anda Iviana Juniani; Dian Asa Utari (Proceedings Conference On Design Manufacture Engineering And Its Application, 2024)
Projects are a series of production processes that produce certain outputs within a specified time period. Compactor Roller Compact Mould implemented by one of the manufacturing companies in Sidoarjo has experienced delays from the deadline that has been set. This delay is caused by ineffective planning and scheduling, which results in the completion of other projects being delayed. The project consists of many overlapping sub-activities. Therefore, this research was conducted to reschedule each overlapping activity using the Precedence Diagram Method (PDM). The results showed that projects with many activities can be decomposed using network planning to plan each activity in the project. Thus, in future research, this network planning can be used to identify which set of activities takes the longest time and can be analyzed further to speed up the processing time of sub-activity tips on the project.